Pengaruh Penerapan Etika Bisnis Islam Terhadap Loyalitas Pelanggan dengan Kepuasansebagai Variabel Intervening Pada Pedagang di Pasar Tradisional Kelurahan Sengeti - Kurnia Sari Rahma; Agustina Mutia; Awal Habibah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Islamic business ethics in trading activities is very important so as not to take actions that deviate from Islamic teachings. In the business world, competition among fellow traders to maintain customer satisfaction and loyalty is a natural thing, if you look positively at business competitors not as a threat but as a motivation to move forward. The objectives of this study are 1) to determine the direct effect of the application of Islamic business ethics on customer loyalty, 2) to determine the direct effect of the application of Islamic business ethics on customer satisfaction, 3) to determine the direct effect of satisfaction on customer loyalty, 4) to determine indirectly the application of Islamic business ethics on customer loyalty through satisfaction.The method used in this research is a quantitative method using path analysis with a sample respondent of 97 respondents. This analysis is used to see the direct and indirect effects between variables, the results of this study indicate that 1) directly Islamic business ethics has a positive and significant effect on customer loyalty, 2) directly Islamic business ethics has a positive and significant effect on customer satisfaction, 3) directly customer satisfaction has a positive and significant effect on customer loyalty, 4) indirectly Islamic business ethics has no positive and significant effect on customer loyalty through satisfaction. As for after the application of Islamic business ethics by traders, there is a separate satisfaction in customers that creates customer loyalty, namely by deciding to buy from traders, customers make repeat purchases and recommend to others, although there is still one customer who has not recommended to others. so it can be concluded that Islamic business ethics applied by traders have been able to maintain customer satisfaction and loyalty in Sengeti Market.